Golden years : what I've learned from love, loss, and reality TV - Turner, Gerry, 1951- (Grand Central, 2025)
"When his high school sweetheart and wife of over forty years passed away unexpectedly, Gerry Turner's life was indelibly changed. In that moment, his and Toni's shared vision of living out their retirement together was shattered. In the wake of this profound loss, Gerry had to move forward--for himself, for his daughters, and for Toni. After years of grieving and uneven healing, Gerry finally felt ready to find the next woman he couldn't live without--to help him take on new adventures and live out his golden years the way Toni would have wanted him to. When he applied to star in ABC's The Golden Bachelor, he had no idea just how much his life was about to change. In Golden Years, Gerry chronicles his grief after Toni's death, his unbelievable experiences on The Golden Bachelor, and the life-altering lessons he took away from both." -- book jacket.